Korelasi Daya Ingat Peserta Didik dengan Capaian Hasil Belajar pada Siswa Kelas IV di SDN Pojok Klitih Kota Jombang - Ni'matul Izza; Nilna Rahmayanti; Ahmad Giri Ainuddin M (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
Memory capacity is an important cognitive component in students’ ability to receive, retain, and process information during learning. This capacity is particularly relevant to mathematics learning, in which students are required to retain concepts and retrieve previously learned information to support their understanding of new material. This study examines the relationship between students’ memory capacity and mathematics learning outcomes among fourth-grade students at SDN Pojok Klitih, Jombang City. A quantitative approach with a correlational design was employed, involving 32 fourth-grade students. The data were analyzed through normality and linearity tests, followed by Pearson’s Product-Moment correlation and a t-test at the 0.05 significance level. The findings indicate that students’ memory capacity was in the high category, with a mean score of 81.09, while their mathematics learning outcomes were likewise categorized as high, with a mean score of 76.31. The correlation analysis revealed a positive and statistically significant relationship between memory capacity and mathematics learning outcomes (r = 0.429, p = 0.014), indicating a moderate association between the two variables. This finding was further supported by the t-test, which yielded a calculated t-value of 2.601, exceeding the critical value of 2.042. These results demonstrate that memory capacity is significantly associated with students’ mathematics learning outcomes. The findings highlight the relevance of cognitive factors, particularly memory capacity, in understanding variations in mathematics achievement among elementary school students.